Clinico pathological profile of carcinoma breast in Odisha: a mining state of eastern India - Samanta, Dipti Rani; Senapati, Surendra Nath; Rout, Suresh Kumar; Dash, Tapas Kumar (International Journal of Research in Medical Sciences, 2021)
Background: Carcinoma of the breast is the commonest malignancy in indian women. It is a serious health issue, producing increased mortality among indian women. Breast carcinoma is a heterogeneous disease with wide difference in clinico pathological presentation in different parts of the world. This study had been undertaken to evaluate the clinico pathological presentation of carcinoma breast in Odisha which is one of the important mining belts of eastern India. Methods: It was a retrospective analysis of 1000 eligible histopathology proved non metastatic, post-operative carcinoma breast, treated at Acharya Harihar post graduate institute of cancer, a tertiary cancer hospital of Odisha. The data were retrieved with respect to clinical presentation, pathological finding, stage of the disease and receptor status of the cancer breast patients from the hospital records. Results: Among 1000 patients the mean age of presentation was 47.25 years, among them 99.2% of the patient were female. Upper outer quadrant lesion was 66.6%. 96.5% of patient presented with invasive duct carcinoma (IDC). Multicentricity was 1.9%. 36.5% presented with lympho vascular space invasion and 23% with perineural invasion. Mean tumor size was 4.24±2.07. 59.6% patient had lymph node involvement. Mean number of lymph node positive was 3.67. Extracapsular invasion was 19.9%. Majority of the patient presented with advanced stage of the disease. ER+, PR+, HER-2 neu negative breast cancer was only 21.5%, triple negative 47.9%, ER-, PR- HER-2 neu ± 15.2%, triple positive 9.1%. Conclusions: The patient of carcinoma breast in this part of world presented at younger age with advanced stage of the disease having triple negativity and HER-2 neu positive in a greater number of patients which are biologically aggressive, needs early detection and aggressive treatment.